2017
DOI: 10.1016/j.pss.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

New members of Datura family

Abstract: Asteroid families are groups of minor planets which have a common origin in catastrophic disruptions. Young asteroid families are very interesting because they represent the product of their parent body's fragmentation before orbital and physical evolutionary processes could have changed them. A group of minor asteroids associated with the largest body Datura (1270) is of particular interest because it has enough known members and resides in the inner part of the main asteroid belt and is easy to observe. Up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
(26 reference statements)
0
9
0
1
Order By: Relevance
“…Datura family.-Historically, a compact cluster of six small asteroids about (1270) Datura (thence the Datura family) was the first example of a very young family discovered . Its convenient location in the innermost part of the main belt, and large orbital eccentricity of ≃ 0.21 (thence low perihelia), allowed to quickly increase Datura's known population to the present-day census of 76 (see gradual steps in Vokrouhlický et al, 2009;Rosaev and Plávalová, 2017;Vokrouhlický et al, 2017a). Fig.…”
Section: Very Young Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Datura family.-Historically, a compact cluster of six small asteroids about (1270) Datura (thence the Datura family) was the first example of a very young family discovered . Its convenient location in the innermost part of the main belt, and large orbital eccentricity of ≃ 0.21 (thence low perihelia), allowed to quickly increase Datura's known population to the present-day census of 76 (see gradual steps in Vokrouhlický et al, 2009;Rosaev and Plávalová, 2017;Vokrouhlický et al, 2017a). Fig.…”
Section: Very Young Familiesmentioning
confidence: 99%
“…Finally, despite the compactness of the Datura family, the orbital history of some of its members happens to interact with a weak, high-order, mean motion resonance M9/16 with Mars (see already . Various aspects and illustrations of the resonant dynamics in M9/16 has been studied by Rosaev and Plávalová (2017) and more recently by Plávalová and Rosaev (2021). In general, such orbits present dynamical chaos effects that undermine their use for the family age determination based on regular-orbits convergence.…”
Section: Very Young Familiesmentioning
confidence: 99%
“…Until recently, only seven members of the Datura family were known (Nesvorný et al , 2015Vokrouhlický et al 2009), all of them belonging to the so-called S-type of minor planets (Tholen 1984). According to our latest analyses (Rosaev & Plávalová 2017), however, three new members have to be included, and Vokrouhlický et al (2017) have reported on the existence of another seven. The total sum of known members of the Datura family might therefore be as high as 17 at the time of writing (see Table 1).…”
Section: Datura Family Main Factsmentioning
confidence: 99%
“…This relatively young age makes this family a very interesting group that can provide important insights into largescale fragmentation and other physical processes that affect asteroids after their formation. Rosaev & Plávalová (2015) found three new members of the Datura family, and later Vokrouhlický et al (2017) presented a wealth of new data on that family: they extended its population to 17 members and two candidate members. They were able to derive spins for the six largest members and shapes of the four largest known members.…”
Section: The Datura Familymentioning
confidence: 99%